Winnipeg’s Pediatric Cardiac Inquest: The Patient’s and Parent’s Advocate - Borton, Joan (Operating Room Nurses Association of Canada Journal, 1999)
What happened in 1994 is an extreme example of what could happen to any nurse, in any health care institution anywhere in Canada. It is amazing to me that people now want to interview us and hear us speak, because in 1994 it seemed that no one looked upon us as someone to be listened to, respected or even believed.